Nouveau stade et décision publique : la controverse autour de l’écrin de l’Union Saint-Gilloise - Olivier Paye; Loïc Cobut; Youri Lou Vertongen; Lou Kervarrec; Thomas Laloux; Thomas Ermans (Brussels Studies)
Unlike many French and British cities over the last few decades, Brussels has never seen the construction of a professional football stadium. The recent failure to build a new “national stadium” at Heysel has left its mark in people's minds. In recent years, however, a new project was launched to the benefit of Union Saint-Gilloise, which was promoted to Division 1 in 2021 and became Belgian champion in 2025. The club, which has been based in Forest for over a century, has ambitions to build its new home on a plot of land owned by the municipality on the edge of the Brussels region. Following a sequential approach to public policy analysis, this article traces the phases of the public decision-making process during the 2018-2024 municipal term. It explains the terms of a controversy which has yet to be resolved in mid-2025, with the project still awaiting a favourable decision from the authorities. Its conclusion examines the extent to which certain hypotheses put forward to explain the failure of the national stadium project at Heysel can also explain the stagnation of the project for a new stadium at Bempt.